2014
DOI: 10.1002/cam4.195
|View full text |Cite
|
Sign up to set email alerts
|

Galectin‐7 as a potential predictive marker of chemo‐ and/or radio‐therapy resistance in oral squamous cell carcinoma

Abstract: Treatment of advanced oral squamous cell carcinoma (OSCC) requires the integration of multimodal approaches. The aim of this study was to identify predictors of tumor sensitivity to preoperative radiotherapy/chemotherapy for OSCC in order to allow oncologists to determine optimum therapeutic strategies without the associated adverse effects. Here, the protein expression profiles of formalin-fixed paraffin-embedded (FFPE) tissue samples from 18 OSCC patients, termed learning cases, who received preoperative che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 30 publications
1
23
0
Order By: Relevance
“…Consistence with reports in breast, ovarian and oral squamous cell carcinoma [19, 22, 23], elevated galectin-7 expression acted as a reverse predictive factor in non-metastasis ccRCC patients. This finding may result from the function of galectin-7 in enhancing tumor cells aggressiveness and inducing chemo-resistance [19].…”
Section: Discussionsupporting
confidence: 62%
“…Consistence with reports in breast, ovarian and oral squamous cell carcinoma [19, 22, 23], elevated galectin-7 expression acted as a reverse predictive factor in non-metastasis ccRCC patients. This finding may result from the function of galectin-7 in enhancing tumor cells aggressiveness and inducing chemo-resistance [19].…”
Section: Discussionsupporting
confidence: 62%
“…Matsukawa et al (18) reported previously that adenoviral delivery of the galectin-7 gene may induce modest apoptosis and reduce the viability of human OSCC HSC3 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recent study on oral SCC showed that galectin-7 can act as potential predictive marker of chemo/radio therapy resistance in this cancer. Oral SCC cell line showed decreased cell viability with elevated expression of galectin-7 (Matsukawa et al, 2014).…”
Section: 455 Expression and Roles Of Galectin-7 In Different Types Omentioning
confidence: 99%